Does corporate social responsibility influence the corporate performance of the U.S. telecommunications industry? - Wang W.-K.; Lu W.-M.; Kweh Q.L.; Lai H.-W. (Elsevier Ltd, 2023)
This study uses a two-stage approach to explore the relationship between the operational performance of U.S. telecommunications companies and their implementation of corporate social responsibility (CSR). In the first stage, this study adopts the dynamic data envelopment analysis model to measure the efficiency of the telecommunications industry in the U.S. from 2004 to 2008. The empirical results show that the corporate efficiency of those companies that implemented CSR was higher than that of those companies that did not. In the second stage, the study adopts OLS and 2SLS to explore the influence of the execution level of CSR on performance. The results show that the Kinder, Lyndenberg, and Domini & Co (KLD) social ratings indexes are significantly and positively related to corporate performance. Finally, this study suggests ways in which corporate policy makers can enhance CSR in order to improve corporate performance in the U.S. telecommunications industry. © 2014 Elsevier Ltd.